Methods and Areas of Application of Information and Communication Technology (ICT) in Teaching and Learning of Economics in Colleges of Education in North Central States, Nigeria - Musa, Okekwu Ate; Tokshik, Gaius Mashor (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
The main purpose of this study was to find out the methods and areas of application of Information and Communication Technology in teaching and learning of Economics in Colleges of Education in North Central States, Nigeria. The study was guided by two purposes, two research questions and two null hypotheses. The researcher adopted descriptive survey research design. The study was carried out in North Central States, Nigeria. The population comprised 140 Economics Lecturers and 87) NCE III students from selected Colleges of Education in North Central States. Stratified sampling technique was used to draw a sample size of 114 NCE III students and the 140 lecturers were retained. Observation Checklist on Available ICT Facilities for Teaching and learning Economics and a structured questionnaire were used for data collection. The reliability of the instrument was ascertained using Cronbach Alpha and an overall reliability coefficient of .97 was ascertained. Frequency, percentage, mean and standard deviation were used to answer research questions while independent sampled t-test was used to test null hypotheses at 0.05 level of significant. The Findings of this study showed that Lecturers and students agreed that expository/transmission method, inquiry method, simulation method, problem solving method and discussion method are use in teaching and learning of Economics at colleges of education. recommendation and suggestion for further studies were made.